Methods of using Laser Radiation and Devices in Eliminating Eye Defects (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article presents the physical and biological rationale for the use of laser radiation in the correction of the most common defects of the human eye, nearsightedness (myopia) and farsightedness (hyperopia). The technologies of excimer lasers and femtosecond lasers used in these diseases are highlighted, and their differences from previously used methods are shown.